It matters what you measure: a systematic literature review examining whether young people in poorer socioeconomic circumstances are more at risk of chlamydia. Issue 2 (11th October 2012) - Sheringham, Jessica; Mann, Sue; Simms, Ian; Stafford, Mai; Hart, Graham J; Raine, Rosalind
Abstract : Background: England has invested in chlamydia screening interventions for young people. It is not known whether young people in poorer socioeconomic circumstances (SEC) are at greater risk of chlamydia and therefore in greater need of screening. Objective: To conduct a systematic review examining socioeconomic variations in chlamydia prevalence or positivity in young people. Data sources: Eight bibliographic databases using terms related to chlamydia and SEC, supplemented by website and reference searches. Eligibility: Studies published 1999–2011 in North America, Western Europe, Australia or New Zealand, including populations aged 15–24 years, with chlamydia prevalence or positivity diagnosed by nucleic acid amplification testing. Appraisal and synthesis: Two reviewers independently screened references, extracted data, appraised studies meeting inclusion criteria and rated studies as high, medium or low according to their quality and relevance. Socioeconomic variations in chlamydia were synthesised for medium/high-rated studies only. Results: No high-rated studies were identified. Eight medium-rated studies reported variations in chlamydia prevalence by SEC. In 6/8 studies, prevalence was higher in people of poorer SEC. Associations were more often significant when measured by education than when using other indicators. All studies measuring positivity were rated low. Across all studies, methodological limitations in SEC measurement were identified. Conclusions: The current literature is limited in its capacity to describe associations between SEC and chlamydia risk. The choice of SEC measure may explain why some studies find higher chlamydia prevalence in young people in disadvantaged circumstances while others do not. Studies using appropriate SEC indicators (eg, education) are needed to inform decisions about targeting chlamydia screening.